EFIKASI DIRI MAHASISWA JURUSAN PENDIDIKAN SEJARAH DALAM MATA KULIAH PROGRAM PERENCANAAN PENGAJARAN (P3) - Liana, Corry (Metafora: Education, Social Sciences and Humanities Journal, 2015)
Self-efficacy is the confidence that owned by someone, it able to organize and take action to solve problems and addressing the changes properly. Individuals who have high self efficacy would be able to judge their self, and this will affect the degree of resistance to a task that must be carried out. In the world of education, teachers who have self-efficacy will have strong beliefs, feel comfortable with their self, and be able to control their emotions. That things will make the teachers were able to set up conditions in the classroom properly, able to choose and use appropriate learning strategies, and able to motivate students. Self-efficacy can be developed through Performance experience, vicarious experience, verbal persuasion, and psychological state. Self-efficacy can be forged in early learning, so for the teachers the first years is the most decisive. The Teaching Planning Program or Program Perencanaan Pengajaran (P3) courses, is the beginning of students to teaching and learning at the front of the class, so applying the self efficacy on history education students is the right thing.